S127 Anti-protein serological responses to Streptococcus Pneumoniae, in diverse populations. (2nd December 2011) - Wilson, R J; Cohen, J M; Hyams, C; van Wamel, W J; de Vogel, C; van Belkum, A; Gordon, S B; Brown, J S
Abstract : Although vaccine-induced immunity to Streptococcus pneumoniae depends on anti-capsule antibody responses, naturally acquired adaptive immunity may also depend on antibody against surface protein antigens. Unlike capsular antigen, protein antigens are often highly conserved between S pneumoniae strains and thus could be effective vaccines against all S pneumoniae capsular serotypes. We have investigated the pattern of naturally acquired antibodies to S pneumoniae protein antigens in diverse populations and assessed whether they could be protective. Immunoblots against lysates of wild-type and mutant S pneumoniae with sera from adult humans demonstrated antibody responses to a large number of protein antigens including PspC, PspA and PhtD. Using a multiplex assay of 18 recombinant pneumococcal antigens conjugated to fluorescent beads (xMAP) we made semi-quantitative assessments of serological responses in sera obtained from individuals from the UK and Malawi, as well as in commercial immunoglobulin (IVIG) preparations, pooled from donors in either Europe or USA. All individuals, in both geographical populations had significant levels of antibody to a number of pneumococcal proteins. Individuals varied in their response to specific pneumococcal antigens, with absent responses to some antigens that were dominant in other subjects. However, pooled sera from Malawi and IVIG products from both Europe and the USA had remarkably similar patterns of antigen dominance, with consistently high levels of antibody responses to the antigens PhtD, PspC, PspA and PsaA and weak responses to PilusA, Eno, NanA and SlrA. To investigate the functional importance of these protein antigens we used in vitro flow cytometry assays of complement deposition and neutrophil phagocytosis using bacteria which had been incubated in serum pre-treated with the enzyme IdeS (Immunoglobulin-G degrading enzyme of S. pyogenes, which selectively cleaves IgG). Complement deposition and neutrophil phagocytosis of unencapsulated S pneumoniae TIGR4 strain was reduced in IdeS treated serum compared to untreated serum. These data demonstrate that there are naturally acquired functionally significant antibody responses to a range of conserved S pneumoniae protein antigens. The same antigens induce responses in diverse populations, suggesting that these protein antigens would be useful components for a polyvalent protein vaccine that is broadly protective against S pneumoniae infections.